The Role of Constitutional Law in Environmental Protection: Government Obligations and Legal Frameworks for Sustainable Development - Satria, Rahmad (Journal of Law and Humanity Studies, 2025)
This article explores the critical role of constitutional law in environmental protection, emphasizing the obligations of governments and the legal frameworks necessary for sustainable development. Utilizing a qualitative approach through extensive literature review, the study examines various constitutional provisions across different jurisdictions that enshrine environmental rights and responsibilities. It highlights how these legal frameworks serve as foundational instruments for promoting environmental sustainability and ensuring government accountability in environmental governance. The findings reveal that constitutional law not only provides a basis for environmental protection but also empowers citizens to hold their governments accountable for environmental degradation. Furthermore, the article discusses the interplay between constitutional law and international environmental agreements, illustrating how domestic legal frameworks can align with global sustainability goals. By analyzing case studies and existing literature, this research underscores the importance of integrating environmental considerations into constitutional law to foster a more sustainable future. The study concludes with recommendations for policymakers to enhance constitutional provisions related to environmental protection, ensuring that governments fulfill their obligations towards sustainable development. This research contributes to the ongoing discourse on the intersection of law and environmental sustainability, advocating for stronger legal frameworks that prioritize ecological integrity within constitutional mandates.